The Redundant Design and Reliability Analysis of Magnetic Bearings Used for Aeroengine. (18th June 2014) - Wang, Xiaoguang; Liu, Qian; Hu, Yefa; Cheng, Xin; Chen, Haohui; Huang, Longfei
Abstract : The redundant design principle of weak coupling magnetic bearing system for aeroengine is put forward. A redundant design scheme of weak coupling magnetic bearing system is provided including radial and axial magnetic bearings and their control system. The performance of the weak coupling redundant magnetic bearing is analyzed with the finite element method and then compared with the strong coupling redundant magnetic bearing. The weak coupling redundant magnetic bearing has some advantages in both redundancy and load bearing capacity under the circumstance of either no failure or partial failure in the coils. In view of the increase in the number of electronic components in the control system, both reliability and redundancy are evaluated comprehensively. A compromise solution of 12-pole structure for the weak coupling redundant magnetic bearing is recommended.